Social monogamy and egg production in the snapping shrimp Alpheus brasileiro (Caridea: Alpheidae) from the south-eastern coast of Brazil. (30th June 2016) - Pescinelli, Régis Augusto; Davanso, Thiago Maia; Costa, Rogério Caetano
Abstract : This study tested for social monogamy in Alpheus brasileiro Anker, 2012. We also analysed egg production in this species. Sampling was conducted bimonthly from March 2013 to January 2014, and specimens were collected manually in the intertidal estuarine zone of Cananéia, São Paulo, Brazil. A total of 186 specimens (92 males and 94 females) were captured, and 46% of them were found living in heterosexual pairs. The carapace length (CL mm) of paired males and females was positively correlated. We analysed 35 females carrying eggs underneath the abdomen: 28 of these females had eggs in stage I of development, four had eggs in stage II, and three had eggs in stage III. The average (±SD) mean fecundity for females carrying early (stage I) eggs was 149 (±93) eggs. Egg volume differed significantly among developmental stages, with a 35.4% increase in egg volume between stages I and III. The egg volume and size (CL) of females correlated positively. A positive correlation between the number of eggs and carapace length was found, with a proportional increase in the number of eggs according to the size of females. Our results suggest that the studied population of A. brasileiro is socially monogamous and provide the first insights into egg production in this species.